Onderwijs voorbij de meritocratie: Tegendraadse beschouwingen over prestaties in het onderwijs (Radboud University Press, 2025)
Performance, performance, performance. Education is suffering from performance pain that is becoming increasingly severe. Can students, teachers and schools meet the increasing performance obligations? If we can hardly get any further with even more effort for better performance, what can we do?“Onderwijs voorbij de meritocratie” looks at the underlying meritocratic ideal of one's own merits for the issue of performance and questions it. The meritocratic ideal is indeed attractive, but in today's society and in today's education that ideal has become tyrannical. Meritocracy undermines solidarity and undermines human dignity.Questions addressed include: how did the meritocratic ideal find its way into education? What is its significance for working on equal opportunities and why does it miss its target? How can schools realise education and equal opportunities beyond meritocracy? What are useful and relevant alternatives to the one-sided pursuit of one's own merits? What do education administrators, school leaders, teachers and other stakeholders have to do to achieve this?“Onderwijs voorbij de meritocratie”contains eleven academic contributions and six practical contributions that challenge and enrich the imagination about good education. The authors are nourished by sources from philosophy, pedagogy and theology.The collection is for courageous people in education, society and politics.